Remnant lipoproteins play an important role of in-stent restenosis in type 2 diabetes undergoing percutaneous coronary intervention: a single-centre observational cohort study - Zheng Qin (Cardiovascular Diabetology, 2019)
Abstract Background Increasing evidence has suggested that the presence of remnant lipoproteins is a significant risk factor for atherosclerosis. Remnant lipoproteins are lipoproteins that are rich in triglycerides (TGs), and the main components include very-low-density lipoprotein (VLDL) in the fasting state. Diabetic patients often have hypertriglyceridemia with elevated levels of VLDL cholesterol but normal levels of low-density lipoprotein cholesterol (LDL-C). The aim of the present study was to elucidate the potential role of remnant lipoproteins-induced atherosclerosis in the occurrence and development of in-stent restenosis (ISR) in diabetic patients with coronary artery disease. Methods The present study enrolled 2312 patients with type 2 diabetes mellitus who underwent percutaneous coronary intervention from January 2013 to December 2014 and who were followed up by angiography. Patients were divided into two groups based on the presence or absence of ISR, and multivariate Cox’s proportional hazards regression modelling showed that remnant-like particle cholesterol (RLP-C) was an independent risk factor for ISR. According to the receiver operating characteristic curve, the optimal cutoff point of the RLP-C was identified, and the patients were further divided into 2 groups. Propensity score matching analysis was performed, and 762 pairs were successfully matched. Log-rank tests were used to compare Kaplan–Meier curves for overall follow-up to assess ISR. Results The multivariate Cox’s proportional hazards regression analysis showed that RLP-C was independently associated with ISR, and the baseline RLP-C level at 0.505 mmol/L was identified as the optimal cutoff point to predict ISR. Patients were divided into 2 groups by RLP levels. After propensity score matching analysis, a total of 762 pairs matched patients were generated. Kaplan–Meier curves showed that the estimated cumulative rate of ISR was significantly higher in patients with RLP-C levels ≥ 0.505 mmol/L (log-rank P < 0.001; HR equal to 4.175, 95% CI = 3.045–5.723, P < 0.001) compared to patients with RLP-C levels < 0.505 mmol/L. Conclusions The present study emphasized the importance of remnant-like particle cholesterol in cardiovascular pathology in diabetic patients. Physicians should take measures to control RLP-C below the level of 0.505 mmol/L to better prevent of in-stent restenosis in diabetic patients.